Congenital perineal hamartomas with rectal duplication: A case report - Zhang, Yixin; Zhang, Mo; Ma, Wei; Yuan, Zhengwei; Wang, Dajia; Chen, Lizhu (Frontiers in Medicine, 2023)
Background Congenital perineal hamartomas are rare, and reports of prenatal ultrasound diagnosis are limited. Perineal hamartomas are usually associated with other structural malformations, which complicate the therapeutic regime. Case presentation We report a case of perineal hamartomas associated with rectal duplication in a female fetus. A review of the literature on similar cases was also presented. A fetus was first diagnosed with a perineal mass at 33 weeks of gestation using ultrasound examination in our hospital. Two-dimensional ultrasonography showed a hyperechoic mass resembling a scrotum in the perineum of the fetus. The pedicle connected the mass to the fetal anus. The masses were excised after birth, and perineal hamartomas were confirmed by pathological diagnosis. Rectal duplication, an associated malformation, was found during the surgery. The rectal duplication cyst was removed at the same time. Conclusion Congenital perineal masses are rare and are usually associated with urogenital and anorectal malformations. Prenatal ultrasound should be used to assess the position and relationship between the mass and perineal organs, and to exclude other combined deformities.